Dominant Factors Behavioral Intention Of The Generation Millennials in Using E-Wallets - Nana Triapnita Nainggolan; Fitria Halim; Sofiyan Sofiyan; Ady Inrawan; John Lidia (Research Synergy Foundation, 2023)
Technological advancements fueled by the internet revolution have transformed the financial services industry's image, resulting in modifications to electronic financial services. These service changes can be seen in almost all forms of financial services, such as banking, insurance, and stock trading, which are carried out using electronic media, such as E-wallets services. The primary purpose of this study is to determine the behavior of the Millennial class for digital wallet applications in terms of perceived ease of use, perceived usefulness, trust, social influence. This study utilized a quantitative method using exploratory surveys and online questionnaires, as well as a literature and field research design. For data analysis, this research uses the Smart PLS application with the PLS-SEM approach oriented. Data was collected using non-probability sampling using a purposive sampling approach, yielding a sample size of 146 respondents for this research. This research provides information about the behavior of using digital wallet applications, which are significantly influenced by perceived ease of use, trust, and social influence. Furthermore, the Perceived Usefulness factor does not significantly impact the behavior of using digital wallet applications. These findings highlight the importance of trust as a motivator for customers when utilizing an E-Wallet application. It is preferable to expand the number of study samples in order to appropriately generalize findings, as well as to include research factors that are believed to influence behavioral intention to use. This research will look at the effects of perceived ease of use, perceived utility, trust, and social influence on Generation Millennial behavior when it comes to using digital wallets.